Wastewater Collection Performance on Communal Sanitation System in Cimahi Indonesia - Mohamad Rangga Sururi; Siti Ainun; Fikri Abdillah (Jurnal Sains & Teknologi Lingkungan, 2017)
In dense population cities, the effectiveness of the communal system in handling municipal domestic wastewater is important. This research aimed to evaluate the effectiveness of pipe dimensioning process and determine it as a wastewater collector to be served as a reactor through a tracer test. Thus, this work may give some inputs for a reliable design criteria for communal system in Indonesia. The reaserch area was at communal system on Tegal Kawung RT 05 RW 08. It served 37 household which was identified using built drawings and field checking. The number of communal septic tank user was 150 people who approximately use water of 134.33 L/person/day and more than 75% (107.46 L/persons/day )was discharged to the system. The tracer test was done between the control box with the distance of 27.94 m and diameter of 150 mm. Based on the mathematical model that was used, the diameter of the pipe should be 100 mm. The tracer test showed that the piping system is the Plug Flow Reactor but it is not yet effective, shown by the MDI value of 3.36.